A critical review of container security operations. Issue 2 (17th February 2017) - Zhao, Xiaowei; Yan, Hong; Zhang, Jiantong
ABSTRACT: Containers, which permit fast and safe handling between modal systems, are the main equipment used in intermodal transport. Unfortunately, enhancement of the efficiency and velocity of container operations has created a breach in traditional security, also known as container security. This paper presents a critical literature review of container security operations. We aim to identify current trends and future research directions in container security. We propose a classification framework based on the following elements: presenting the container security perspective, identifying threats, evaluating container security, balancing costs/benefits and the degree of security, balancing time savings/reduction and the degree of security, and securing containerized transportation processes. We discuss the current studies of these problems, the methodologies adopted and important insights into container security.